ANALISIS DESKRIPTIF LINGKUNGAN KERJA YANG MENDUKUNG CAPAIAN KINERJA DOSEN - Wahyudi Wahyudi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
Teaching, researching, community service, and other activities are routines carried out involving many parties, both leaders and colleagues, in the implementation of which they directly affect the feelings or psychology of a lecturer. The better the response of the parties involved, it is possible to increase the performance among the lecturers who work together. This study aims to analyze the opinion of Pamulang university lecturers about the work environment that is considered to have an effect on improving lecturer performance. Given the nature of this research is descriptive, the research method uses qualitative. The object of this research is the management study program at Pamulang University, with a lecturer analysis unit. The basis for determining correspondence is purposive, with the fulfillment of a number of criteria. The results showed that the work environment in the Unpam undergraduate management study program was quite good, especially in research performance. That is, the existing work environment has a spirit of enthusiasm for achieving performance.